Effects of Yoga in Parkinson’s Disease: A Systematic Review of Randomized Controlled Trials - Giridharan, Selvaraj; Ansari, Jawaher; Pannerselvam, Hari; Godbole, Mrunmai (International Research Journal of Ayurveda & Yoga, 2025)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms that diminish the quality of life (QoL). While pharmacological interventions target dopamine deficiencies, they often fail to address non-motor symptoms such as anxiety and depression. Yoga, a mind– body practice that includes posture, breathing techniques, and meditation, has gained recognition as a promising complementary therapy. This systematic review synthesized randomized controlled trials (RCTs) to assess the impact of yoga on motor and non-motor symptoms, QoL, and safety in PD patients. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram guidelines, we searched PubMed, Embase, Cochrane Library, Scopus, and Web of Science for RCTs published between January 2020 and April 2025. The inclusion criteria were adult participants with idiopathic PD, yoga as the primary intervention, and comparisons with active or passive control groups. The outcomes assessed included motor function, non-motor symptoms (e.g., anxiety and depression), QoL, and adverse events. The risk of bias was evaluated using the Cochrane Risk of Bias 2 tool, and evidence certainty was appraised using the Grading of Recommendations Assessment, Development, and Evaluation approach. Due to heterogeneity, a narrative synthesis was conducted. Results: Seven RCTs, involving 475 participants with mild-to-moderate PD, analyzed hatha or mindfulness yoga interventions over 6–12 weeks. The findings showed that yoga significantly improved motor symptoms with moderate to-large effect sizes. Studies have reported improvements in balance, although the gait effects were inconsistent. For non-motor outcomes, anxiety, and depression showed moderate reductions, while QoL improvements lasted for 6 months. Evidence indicates improvements in biomarkers such as interleukin-6. Yoga was safe with no serious adverse events. Evidence certainty was moderate for motor and non-motor outcomes. Conclusion: Yoga is a safe and feasible adjunct for PD, offering benefits for motor function, mood, and QoL. Larger, standardized RCTs with longer follow-up periods are needed to confirm and optimize protocols.